Pro Windows phone app development - Cameron, Rob (Berkeley, California Apress, 2011)
The Windows Phone 7 platform, now recently updated, provides a remarkable opportunity for Windows developers to create state-of-the-art mobile applications using their existing skills and a familiar toolset. Pro Windows Phone 7 Development, Second Edition helps you unlock the potential of this platform and create dazzling, visually rich, and highly functional applications for the Windows Phone Marketplace?including using new features like copy-and-paste and API improvements in the NoDo and Mango update waves. For developers new to the Windows Phone platform?whether .NET, iPhone, or Android developers?this book starts by introducing the features and specifications of the Windows Phone series, and then leads you through the complete application development process. You'll learn how to use Microsoft technologies like Silverlight, .NET, the XNA Framework, Visual Studio, and Expression Blend effectively, how to take advantage of the device's sensors with the location service, accelerometer, and touch, how to make your apps location-aware using GPS data, how to utilize the rich media capabilities of the Windows Phone series, and much more. Finally, you'll receive a full tutorial on how to publish and sell your application through the Windows Phone Marketplace. And in this second edition, learn quickly and easily how to take advantage of new API capabilities and HTML5 support right in your browser.
Electronic reproduction.
Keywords: Application software -- Development; Windows PowerShell (Computer program language); Smartphones